Evaluating melt foamability of LLDPE/LDPE blends with high LLDPE content by bubble coalescence mechanism. (20th January 2021) - Zhang, Hong; Liu, Tao; Li, Bin; Li, Hui; Cao, Zhihuai; Jin, Geng; Zhao, Ling; Xin, Zhong
Abstract: Bubble coalescence mechanism was introduced to evaluate the melt foamability of polymer blends. Linear low-density polyethylene (LLDPE), with excellent mechanical properties but poor foamability, was blended with small amounts of low-density polyethylene (LDPE), which was expected to impart the desired foaming-related properties to LLDPE. The presence of LDPE in LLDPE matrix provided only a small improvement in linear viscoelasticity under small deformations, but a significantly large improvement in nonlinear behavior under large deformations. A critical coalescence radius curve was simulated using a pressure-balanced bubble growth model to evaluate bubble coalescence and foamability of the blends, taking into account the linear and non-linear behaviors. It was found that the steep stress growth caused by LDPE addition can dramatically increase the pressure of large bubbles and then effectively inhibit the coalescence of adjacent bubbles, thus improving the foamability of LLDPE/LDPE blends. The theoretical predictions derived from the bubble coalescence mechanism were also confirmed by experiments. Graphical abstract: Image 1 Highlights: Presence of LDPE in LLDPE matrix enhanced non-linear viscoelasticity significantly. Foamability of LLDPE/LDPE blends were simulated by critical coalescence curve. Steep stress growth caused by LDPE addition increases the pressure of large bubbles and facilitates good foamability.